2020
DOI: 10.1021/acs.nanolett.0c02548
|View full text |Cite
|
Sign up to set email alerts
|

Metasurface Enhanced Sensitized Photon Upconversion: Toward Highly Efficient Low Power Upconversion Applications and Nanoscale E-Field Sensors

Abstract: Large-scale nanoimprinted metasurfaces based on silicon photonic crystal slabs were produced and coated with a NaYF4:Yb3+/Er3+ upconversion nanoparticle (UCNP) layer. UCNPs on these metasurfaces yield a more than 500-fold enhanced upconversion emission compared to UCNPs on planar surfaces. It is also demonstrated how the optical response of the UCNPs can be used to estimate the local field energy in the coating layer. Optical simulations using the finite element method validate the experimental results and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…Although the local field enhancement provided by dielectric nanostructures is typically smaller than that of plasmonic nanostructures, dielectric nanostructures do not suffer parasitic energy losses manifested by fluorescence quench caused by the metal's electron gas through its many internal degrees of freedom (Joule losses). Through proper design of the structure, some dielectric nanostructures can enhance the UCL of UCNPs more than 100 times [28,[41][42][43][44][45][46][47]. A variety of dielectric nanostructures, such as photonic crystals [28,[41][42][43][44], and metasurfaces [45][46][47] have been employed to enhance the UCL of UCNPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the local field enhancement provided by dielectric nanostructures is typically smaller than that of plasmonic nanostructures, dielectric nanostructures do not suffer parasitic energy losses manifested by fluorescence quench caused by the metal's electron gas through its many internal degrees of freedom (Joule losses). Through proper design of the structure, some dielectric nanostructures can enhance the UCL of UCNPs more than 100 times [28,[41][42][43][44][45][46][47]. A variety of dielectric nanostructures, such as photonic crystals [28,[41][42][43][44], and metasurfaces [45][46][47] have been employed to enhance the UCL of UCNPs.…”
Section: Introductionmentioning
confidence: 99%
“…Through proper design of the structure, some dielectric nanostructures can enhance the UCL of UCNPs more than 100 times [28,[41][42][43][44][45][46][47]. A variety of dielectric nanostructures, such as photonic crystals [28,[41][42][43][44], and metasurfaces [45][46][47] have been employed to enhance the UCL of UCNPs. Recently, we demonstrated that the UCL of UCNPs can be enhanced more than 1000-fold by depositing UCNPs atop a resonant waveguide grating (RWG) structure, also termed 1D photonic crystal substrate, thanks to its guided mode resonance (GMR) to promote the local field of the excitation light atop the RWG [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to convert light from the near-infrared (NIR) to the visible spectral region opens new possibilities to overcome current limitations in solar energy, [1,2] and to enable autofluorescence-free biosensing and -imaging, [3][4][5] temperature sensing (nanothermometry), [6] and nanoscale electric field sensing. [7] Trivalent erbium (Er 3+ )doped crystals are widely used for photon UC as they exhibit ladder-like separated energy levels [8] lying within the nearinfrared biological excitation windows and which are accessible with commercially available excitation sources.…”
Section: Introductionmentioning
confidence: 99%
“…A nowadays widely discussed approach to increase the UC efficiency is to harvest the strongly enhanced near fields in the vicinity of dielectric or plasmonic nanostructures. For photon UC with lanthanide-doped materials, several studies have been published demonstrating more than two orders of magnitude enhanced photon UC upon excitation around 980 nm using plasmonic [12] or dielectric [7,[13][14][15][16] structures. Particularly, Liang et al set a benchmark by the demonstration of five orders of magnitude enhanced UC using a dielectric superlensing array on large areas up to 50 cm 2 .…”
Section: Introductionmentioning
confidence: 99%
“…3a-b, and Table S1). To further investigate the detailed EMU process of Tb 3+ in the sandwich structure Consequently, in the following experiments, we could unveil the variation in steady-state populations 63 of lanthanide excited states before and after the occurrence of Gd 3+ →Tb 3+ inter-shell energy transfer, respectively, by comparing their corresponding UCL intensities of lanthanide. In order to accurately quantify the variations in steady-state populations of lanthanide excited states, the UCL intensities of colloidal solutions of blank sample and sandwich structure NCs well-dispersed in cyclohexane with the same concentration of ~ 1.3 mg/mL (Figs.…”
Section: Resultsmentioning
confidence: 99%